Control de gastos de la empresa Logban Logistica Bananera S.A. 2021 - Ramirez Ramos, Joselyn Alejandrina (2021)
The control of Expenses in a company is made up of a series of important activities that must be constantly taken into consideration, with the aim of acquiring higher profits and in a way preventing the company from having problems as some institutions have. This case study involves the company "LOGBAN" LOGISTICA BANANERA SA, which is dedicated to providing services, design and storage, which leads to the case study EXPENDITURE CONTROL OF THE COMPANY "LOGBAN" LOGISTICA BANANERA SA 2021, based on this an analysis was carried out to identify the shortcomings that the company has through administration and its expenses. Understand the necessary strategies that you must carry out to be able to increase your benefits, make good decisions and based on this, perfect the control of expenses in which it has a deficiency. My research is important because it will help raise awareness among entrepreneurs to plan and budget for each management period.